A comparative study on wear and corrosion behaviour of tungsten carbide-nickel (Wc-Ni) and tungsten carbide-cobalt (Wc-Co) high velocity oxy-fuel (HVOF) for carbon steel blade - Ahmad, Noor Aqilah (2017)
Nowadays, the demand of high wear and corrosion resistance of the components in various industry is increasing from time to time. Therefore, high velocity oxy-fuel (HVOF) thermal spray was introduced to protect machine components from wear and corrosion, to restore worn components and to improve the durability of the components. HVOF is one of the process of depositing a material layer over a base metal or substrate with characteristics of high flame velocity and moderate temperature. The main purpose of this present study is to characterize the structure of the tungsten carbide 10 wt.% nickel (WC-10Ni) and tungsten carbide 12 wt.% w cobalt (WC-12Co) coating deposited by means of HVOF thermal spray onto a continuous digester (CD) blade that made up from carbon steel. The morphology and chemical composition of the coating were characterized by scanning electron microscope (SEM), electron dispersive spectrometer (EDS), and x-ray diffraction (XRD). The hardness test was carried out by using Vickers micro-hardness tester with load of 490.3 mN (0.05 HV). The wear and corrosion behavior and mechanism for both coatings was compared. Three body wear test was carried out in term of weight loss and electrochemical test was performed in acidic media (mixture of sulfuric acid, H2SO4 and ilmenite) to obtain the corrosion rate of the coating. From the result, it shows that WC-12Co coating has finer grain size that is around 2.3 μm. WC-12Co has higher wear resistance due to high volume friction, low mean free path, high hardness and lower porosity distribution compared to WC-10Ni. Besides, the formation of secondary phase, W2C also affected the hardness of both coating, where this phase is harder than WC phase. For corrosion test, WC-12Co shows good corrosion resistance with small differences of corrison rate with WC-10Ni, that is only 0.7016 mm/y. As a conclusion, WC-12Co HVOF coating shows high potential on replacement of CD blade.